DETERMINAN KEJADIAN HIPERTENSI PADA PASIEN PUSKESMAS HARAPAN RAYA PEKANBARU TAHUN 2017 - LPPM Al-Insyirah (Institut Kesehatan dan Teknologi Al Insyirah, 2018)
Hypertension is one of the number one killer diseases in the world today. Age is one of the risk factors of hypertension The normal value of a person's blood pressure with a height measure, weight, Normal activity level and general health is 120/80 mmHg. WHO (World Health Organization) in 2012 the number of cases of hypertension there are 839 million cases. Where this case is estimated to be higher in 2025 with the number of 1.15 billion cases or about 29.2% of the total world population with a target of cases of hypertension in adulthood. This study aims to determine incidence of hypertension in Patients.The type of research used is quantitative analytic observasional. The research design used was cross sectional study. Data analysis was done univariat and bivariate using Chi-Square test. The population in this study were adult patients who visited Harapan Raya Community Health Center. The sample is 91 people.The results showed the value for the incidence of hypertension ie gender variables (p-value = 0.008), History p-value (p-value = 0,013) and physical activity (p-value = 0,000), meaning there is a significant relationship while obesity variable does not show significant relationship (p-value = 0,249).